Pengaruh Faktor Eksposi Terhadap Kualitas Citra Radiografi Thorax Dan Ossa Cruris Pada Pesawat Radiografi Umum Di Rumah Sakit Umum Bina Kasih Medan - Michael, Michael (Lembaga Riset Ilmiah, 2022)
Background: Exposition factors are factors that determine and influence the quality and quantity of x-ray radiation in making radiographic images. In a computed radiography system, images can be optimized before printing, thereby minimizing repetitions caused by inaccuracies. Research Purposes: The aim of this study was to determine the effect of exposure factors on Thorax examination and Os examination. Cruris. Method: This research uses a qualitative method with an observational approach. Researchers collected data by conducting a study of several related literature. Data processing and analysis is carried out by making similarities and differences, conducting a study of literature sources, then analyzing the contents of these sources and concluding the results obtained in order to answer the problem in the problem formulation. Research Results: The Thorax examination used a tube voltage of 64 kV. the tube current is 200 mA, and the exposure time is 0.10 seconds, while in the Os examination. Cruris uses a tube voltage of 50 kV, tube current of 100 mA, and exposure time of 0.12 seconds. Conclusion: Differences in the influence of exposure factors on the Thorax and Os. Cruris is the tube current and second (time), while kV is adjusted to the thickness of the object (atomic number).